Implementation of the Australian core public health functions in rural Western Australia - T. Lower; G. Durham; D. Bow; A. Larson (Elsevier, 2004)
Abstract Objective:To assess the implementation of the Australian core functions of public health in rural Western Australia. Methods:Cross‐sectional surveys (n=26) and semi‐structured key informant interviews (n=64) with public health practitioners throughout each of the eight rural health regions in Western Australia. A scoring system was utilised to categorise responses that were frequently part of current practice (score=2), sometimes undertaken (score=1) and rare or not undertaken at all (score=0). Results:Functions with reasonably good coverage (mean score 31.0) included: preventing and controlling communicable and non‐communicable diseases; promoting and supporting healthy lifestyles; planning, funding, managing and evaluating health gain; ensuring safe and healthy environments; and contributing to healthy growth and development through all life stages. Lower levels of coverage were found for: assessing health needs; developing healthy public policy and fiscal measures; strengthening communities; and improving health for Aboriginal people and other vulnerable groups. Conclusions:There are limitations in the capacity of the rural public health workforce in Western Australia to implement the core public health functions. While some areas were defined as being adequately addressed, gaps in implementation appeared across all nine functions. Implications:The Australian core functions can be utilised to broadly assess current public health practice, however further development of the functions and their measurement, plus methods to align accountability measures for current public health practice with the core functions, are required.